The Evidence of SARS-CoV-2 Human-to-Pets Transmission in Household Settings in Bosnia and Herzegovina - Goletic, Sejla; Goletic, Teufik; Softic, Adis; Zahirovic, Amir; Rukavina, Dunja; Kavazovic, Aida; Omeragic, Jasmin; Umihanic, Sekib; Hukic, Mirsada (Frontiers in Genetics, 2022)
The infection with SARS-CoV-2 virus in cats and dogs raised issue of human-to-animal transmission of SARS-CoV-2 in domestic pets in close contacts with their owners. Our study was designed to research this in the framework of Bosnia and Herzegovina. Using ELISA, AFIAS fluorescent immunoassay, RT-qPCR and WGS on Nanopore MinION platform with ARTIC Network Amplicon sequencing protocol for SARS-CoV-2, we showed that three out of thirteen dogs and one out of five cats from the households with confirmed human cases of COVID-19 in Bosnia-Herzegovina were infected with SARS-CoV-2. The high viral RNA load was detected in samples collected from a 4-year-old male Havanese (Ct=12.52), a 6-year-old German Shepherd (Ct=21.36) and a 9-year-old female American Staffordshire terrier (Ct=25.74). The antibody response in dogs and one cat was observed. The viral genetic sequences from dogs were identical to the sequences detected in the owners suggesting the human-to-animal transmission of the virus. These findings, especially the low initial Ct values detected, from the public health perspective additionally stress the need for precautionary measures to protect both humans and animals.